Asthma: Pharmacological degradation of the airway smooth muscle layer. (September 2020) - Wang, Kimberley C.W.; Donovan, Graham M.; James, Alan L.; Noble, Peter B.
Abstract: Asthma: A disease characterised by excessive and variable airway narrowing, and pathologies of inflammation and remodelling, particularly thickening of the airway smooth muscle (ASM). Treatment approaches dilate narrowed airways and reduce inflammation; however, remodelling seems largely neglected. This review considers the evolution of remodelling in asthma and whether conventional hypotheses that inflammation causes ASM thickening has mislead the medical community into thinking that anti-inflammatories will remedy this ASM defect. There is instead reasonable evidence that ASM thickening occurs independently of inflammation, such that therapies should employ strategies to directly modify ASM growth. Lessons have been learned from the use of untargeted bronchial thermoplasty and there should also be consideration of pharmacological therapies to ablate ASM. We discuss several new approaches to target ASM remodelling in asthma. A major current obstacle is our inability to image the ASM layer and assess treatment response. In this regard, polarisation-sensitive optical coherence tomography offers future promise.